Deteksi Cemaran Bakteri pada Sampel Daging Sapi dengan Uji TPC - Ratu Ayu Ningrat; Ida Bagus Gede Darmayasa; Inna Narayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Balai Karantina Pertanian Kelas I Denpasar is located on Jl. Raya Sesetan No 312, Denpasar which is a place of seclusion and/or action as an effort to prevent the entry and spread of pests and animal diseases or nuisance organisms from abroad and from one area to another within the country, or exit from territory of the Republic of Indonesia. The people's need for beef is increasing, demanding more production in order to reach many consumers in various regions. This causes beef producers to pay attention to the quality of the meat to be marketed so that the meat becomes safe. The Total Plate Count (TPC) is one of the initial tests to identify the general microbial count in meat. Therefore, this study aims to determine the TPC in samples of beef that will be marketed outside Bali. There were 20 samples of beef, originating from 5 beef companies in Bali that beef outside the island of Bali through testing services from the Class 1 Agricultural Quarantine Center Denpasar. The test results stated that most of the beef samples from the five companies were contaminated with microbes. The feasibility of consuming the beef sample was declared feasible in accoaccord per 2008 SNI standard 1 x 106 CFU/g.